Rosiglitazone Use and the Risk of Bladder Cancer in Patients With Type 2 Diabetes. Issue 6 (February 2016) - Han, Eugene; Jang, Suk-Yong; Kim, Gyuri; Lee, Yong-ho; Choe, Eun Yeong; Nam, Chung Mo; Kang, Eun Seok
Abstract : Abstract: Patients with diabetes have a higher incidence of bladder cancer; however, the association between thiazolidinedione use and bladder cancer risk has been controversial. We aimed to investigate whether pioglitazone or rosiglitazone use is associated with bladder cancer risk in patients with type 2 diabetes mellitus. This nationwide nested case-control study used data set obtained from the Korean National Health Insurance Service National Sample Cohort 2002 to 2013. Among the 47, 738 patients with incident diabetes, 85 cases of newly diagnosed bladder cancer and 850 controls (1:10 matched by age, sex, index year, and diabetes diagnosis year) were recruited. Type 2 diabetes mellitus and bladder cancer were diagnosed using the International Statistical Classification of Diseases and Related Health Problems, 10th Revision code. More cases of bladder cancer were diagnosed in men (81.2%), and the stratified age peaked at 70 to 79 years old. Exclusive rosiglitazone use raised the incidence of bladder cancer (odds ratio [OR] = 3.07, 95% confidence interval [CI ] = 1.48–6.37). The risk of bladder cancer started to increase after less than 3 months use (OR = 3.30, 95% CI = 1.02–10.70) and peaked at 3 to 12 months of rosiglitazone use (OR = 4.48, 95% CI = 1.51–13.31). Patients were first exposed to exclusive rosiglitazone within 1 year (OR = 11.74, 95% CI = 2.46–56.12) and those who had consistently used it for 1 year (OR = 4.48 95% CI = 1.51–13.31), had higher risks of bladder cancer compared with nonthiazolidinedione users. Neither pioglitazone use nor exclusive pioglitazone use were associated with an increased incidence of bladder cancer. Rosiglitazone use is associated with an increased risk of incident bladder cancer independent of age and sex in patients with type 2 diabetes mellitus. The highest odds of bladder cancer in rosiglitazone users was seen in those with <1 year of exposure. Abstract : Supplemental Digital Content is available in the text